Evaluating the effects of high penetrations of roof-top wind Turbines on secondary distribution circuits - Kritharas, Petros P.; Ochoa, Luis F. [UNESP]; Papastergiou, Konstantinos D.; Harrison, Gareth P. (Institute of Electrical and Electronics Engineers (IEEE), 2006)
Incentives for using wind power and the increasing price of energy might generate in a relatively short time a scenario where low voltage customers opt to install roof-top wind turbines. This paper focuses on evaluating the effects of such situation in terms of energy consumption, loss reduction, reverse power flow and voltage profiles. Various commercially-available roof-top wind turbines are installed in two secondary distribution circuits considering real-life wind speed data and seasonal load demand. Results are presented and discussed. © 2006 IEEE.
Keywords: distributed generation; distribution networks; line losses; power flow; roof-top wind turbines; Distribution circuits; Line loss; Load demand; Loss reduction; Low voltages; Power flows; Reverse Power flows; Voltage profile; Wind speed data; Distributed power generation; Electric power distribution; Energy utilization; Wind power; Wind turbines; Roofs